2009
DOI: 10.1590/s0103-97332009000400014
|View full text |Cite
|
Sign up to set email alerts
|

Main shocks and evolution of complex earthquake networks

Abstract: Dynamical evolution of earthquake network is studied. Through the analysis of the real data taken from California and Japan, it is found that the values of the clustering coefficient exhibit a specific behavior around the moment of a main shock: the coefficient remains stationary before a main shock, suddenly jumps up at the main shock, and then slowly decreases to become stationary again. Thus, the network approach to seismicity dynamically characterizes main shocks in a peculiar manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…Edges are also de ned in such a way that consecutive seismic events are connected by edges in terms of time. This network model is related to the model presented by Abe and Suzuki (Abe and Suzuki 2009, 2007; Abe et al 2011). They showed that the network of earthquakes is scaleless and has the structure of a small world.…”
Section: Methodology Of Earthquake Networkmentioning
confidence: 55%
“…Edges are also de ned in such a way that consecutive seismic events are connected by edges in terms of time. This network model is related to the model presented by Abe and Suzuki (Abe and Suzuki 2009, 2007; Abe et al 2011). They showed that the network of earthquakes is scaleless and has the structure of a small world.…”
Section: Methodology Of Earthquake Networkmentioning
confidence: 55%
“…Such characteristics of the ARs network are representative of the prescription of the heterogeneous networks (e.g. Abe & Suzuki 2009).…”
Section: Discussionmentioning
confidence: 99%
“…By computing the topological and dynamic characteristics of these networks, earthquake networks have revealed properties, i.e., small-world [ 25 , 26 ], scale-free [ 27 , 28 ] and hierarchical organizations [ 29 ]. In addition, the evolution of network structures indicates there have been precursory seismicity patterns before the occurrence of several earthquakes [ 30 , 31 ]. Therefore, we have attempted to use complex networks to investigate strain observations as a complex system in China, using the multiple YRY-4 borehole strainmeters that have been installed in the Sichuan-Yunnan region since 2008.…”
Section: Introductionmentioning
confidence: 99%